2017
DOI: 10.1111/1365-2664.12951
|View full text |Cite
|
Sign up to set email alerts
|

Effective implementation of age restrictions increases selectivity of sport hunting of the African lion

Abstract: Sport hunting of wildlife can play a role in conservation but can also drive population declines if not managed sustainably. Previous simulation modelling found that large felid species could theoretically be hunted sustainably by restricting harvests to older individuals that have likely reproduced. Several African countries currently use age‐based hunting for lions although the outcomes have yet to be evaluated in a wild population. Here we provide the first empirical evidence that a system of incentives suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The complexity of using the call‐up method is further increased by the recommendation to calibrate a site‐specific response rate by testing with >20 groups of lions, something which is very rarely achieved. For example, in Niassa Reserve, where some of the most extensive call‐up surveys have been conducted—with up to 153 call‐up stations per survey conducted within a year—only 16 prides in total responded (Begg, Miller, & Begg, ). Belant et al () found that lions habituate to call‐up sounds very quickly and that temporal and spatial variation of broadcasted sound did not reduce this habituation (Belant et al, ), which would imply that areas used for calibration cannot subsequently be surveyed.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of using the call‐up method is further increased by the recommendation to calibrate a site‐specific response rate by testing with >20 groups of lions, something which is very rarely achieved. For example, in Niassa Reserve, where some of the most extensive call‐up surveys have been conducted—with up to 153 call‐up stations per survey conducted within a year—only 16 prides in total responded (Begg, Miller, & Begg, ). Belant et al () found that lions habituate to call‐up sounds very quickly and that temporal and spatial variation of broadcasted sound did not reduce this habituation (Belant et al, ), which would imply that areas used for calibration cannot subsequently be surveyed.…”
Section: Discussionmentioning
confidence: 99%
“…Incentive-based quotas have been implemented inside reserves wherein the harvest of a suitably-aged male results in a quota increase for the following year, sometimes quite significantly [ 46 ]. However, reactive quotas still carry the risk the population can decline at a faster rate than the harvest can be adjusted, particularly when hunters increase their effort to confront scarcity [ 46 ]. Secondly, rewarding concessions with higher quotas after harvesting older male could reinforce vacuum effects in lion populations straddling strong gradients of protection.…”
Section: Discussionmentioning
confidence: 99%
“…Around the world, many conservation and natural resource agencies advocate using adaptive management when deciding how to conserve wildlife and ecosystems in the face of uncertainty. A foundational principle of adaptive management is ongoing monitoring of systems as regulations change to generate valuable insight into system functioning that can feedback into future policy formation [ 46 ]. Strong evidence that trophy hunting was driving population declines and skew in lion demography resulted from intensive monitoring of the South Luangwa lion population before and after the hunting moratorium.…”
Section: Discussionmentioning
confidence: 99%
“…Trophy hunting has been found to trigger phenotypic changes in ungulate populations, such as reductions in body weight and size, as well as the dimension and symmetry of horns (Coltman et al, 2003;Douhard et al, 2016;Garel et al, 2007;Pérez et al, 2011;Pigeon et al, 2016). To avoid evolutionary consequences in managed populations (Allendorf, England, Luikart, Ritchie, & Ryman, 2008), harvests should not impose a strong selection (Begg, Miller, & Begg, 2017;Festa-Bianchet, 2016). Yet, it is still debatable (Ripple, Newsome, & Kerley, 2016) whether a properly managed trophy harvest can be used as a conservation tool for maintaining biodiversity (Di Minin, Leader-Williams, & Bradshaw, 2016).…”
mentioning
confidence: 99%